Revisiting Tafsir Hukmi: Unraveling the Legal Interpretation of the Quran and Its Historical Evolution - Nugraha, Sandi; Yunus, Badruzzaman M. (UIN Sunan Gunung Djati Bandung, 2023)
This paper aims to delve deeper into legal interpretation (Tafsir Hukmi) by examining the history of the emergence of legal approaches in the interpretation of the Quran, defining the scope of the term, exploring debates among scholars, and providing examples of Quranic exegesis books adopting legal approaches. The research methodology used is a literature-based descriptive analysis with a historical and exegetical perspective. The results of the study show that legal interpretation (Tafsir Hukmi) is one of the Quranic interpretation styles that employ legal theories and approaches. This approach has its roots dating back to the time of Prophet Muhammad and continued to evolve with the emergence of the school of jurisprudence (Imam Madzhab) scholars who had varying interpretations of Islamic jurisprudence. The scope of the term â€œTafsir Hukmiâ€ encompasses discussions related to the Islamic legal laws in the Quran. Quranic exegesis books following the legal approach can be found within various schools of thought, including Shia Imamiyah, Shia Zaidiyah, Maliki, Hanafi, Hanbali, Shafi'i, and Zahiri.